2005
DOI: 10.1111/j.1572-0241.2005.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Pegylated Interferon alpha-2b Plus Ribavirin in the Retreatment of Chronic Hepatitis C

Abstract: Combination therapy with PEG IFN alpha-2b plus RBV is more effective in patients who relapsed after combination standard IFN plus RBV than in nonresponders to either combination therapy or IFN monotherapy. There was no significant effect of dosing regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 41 publications
9
91
1
3
Order By: Relevance
“…We found a remarkable heterogeneity in the magnitude of the treatment effect among the 14 studies (v 2 for heterogeneity 159.5 with 19 DF; p < 0.0001). The proportion of patients who achieved an SVR differed greatly among the studies, ranging from 7% [5] to 30% [10]. A pooled analysis that excluded both these outliers, reporting the highest [10] and lowest [5] benefit of retreatment, yielded similar results (SVR 15.4%, 95% CI, 8-30%).…”
Section: Sustained Virologic Response Ratesupporting
confidence: 59%
See 3 more Smart Citations
“…We found a remarkable heterogeneity in the magnitude of the treatment effect among the 14 studies (v 2 for heterogeneity 159.5 with 19 DF; p < 0.0001). The proportion of patients who achieved an SVR differed greatly among the studies, ranging from 7% [5] to 30% [10]. A pooled analysis that excluded both these outliers, reporting the highest [10] and lowest [5] benefit of retreatment, yielded similar results (SVR 15.4%, 95% CI, 8-30%).…”
Section: Sustained Virologic Response Ratesupporting
confidence: 59%
“…The main features of the trials included in the meta-analysis are shown in Table 2 in Appendix. Fourteen, which accounted for 3898 patients, were reported as full papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among the trials, three studies did not report the number of participating centers, while all remaining studies were multicenter trials, with the number of centers ranging from 2 to 133; among these studies 8 reported data on the prevalence of patients with cirrhosis (357/1282 = 27.8%).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…If re-treatment is pursued using PEG-IFN at standard doses and RBV 800-1,200 mg/day for 48 weeks, the chance of achieving an SVR may be as high as 40-50% in prior interferon relapsers whereas SVR occurs in up to 30-40% of prior IFN nonresponders and in only 5-12% of prior IFN and RBV nonresponders. [40][41][42][43][44][45][46] In prior IFN and RBV nonresponders, up to 18% achieved SVR with re-treatment using RBV 800-1,400 mg/day combined with PEG-IFN alfa-2b at standard doses for 48 weeks. 46 SVR with re-treatment was lower in patients with genotype 1 infection compared to genotype 2 or 3 infection (SVR 13% and 49%, respectively) and lower in cirrhotics compared to noncirrhotics (SVR 7% versus 16-18% with genotype 1 infection, respectively; SVR 18% versus 38-56% with genotype 2 or 3 infection, respectively).…”
Section: Re-treatment Of Prior Antiviral The-rapy Relapsers and Nonrementioning
confidence: 99%